Transbronchial mediastinal cryobiopsy in the diagnosis of mediastinal lesions: a randomised trial - Zhang, Jing; Guo, Jie-Ru; Huang, Zan-Sheng; Fu, Wan-Lei; Wu, Xian-Li; Wu, Na; Kübler, Wolfgang Michael; Herth, Felix; Fan, Ye (The European respiratory journal, 2021)
Background Guidelines recommend endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) as an initial investigatory technique for mediastinal nodal staging in lung cancer. However, EBUS-TBNA can be limited by the inadequacy of intact tissues, which might restrict its diagnostic yield in mediastinal lesions of certain aetiologies. We have previously shown that EBUS-guided transbronchial mediastinal cryobiopsy can provide intact samples with greater volume. - Methods This randomised study determined the diagnostic yield and safety of transbronchial mediastinal cryobiopsy monitored by endosonography for the diagnosis of mediastinal lesions. Patients with a mediastinal lesion of ≥1 cm in the short axis were recruited. Following identification of the mediastinal lesion by linear EBUS, fine-needle aspiration and cryobiopsy were sequentially performed in a randomised order. Primary end-points were diagnostic yield, defined as the percentage of patients for whom mediastinal biopsy provided a definite diagnosis, and procedure-related adverse events. - Results In total, 197 patients were enrolled and randomly allocated. The overall diagnostic yield was 79.9% and 91.8% for TBNA and transbronchial mediastinal cryobiopsy, respectively (p=0.001). Diagnostic yields were similar for metastatic lymphadenopathy (94.1% versus 95.6%, p=0.58), while cryobiopsy was more sensitive than TBNA in uncommon tumours (91.7% versus 25.0%, p=0.001) and benign disorders (80.9% versus 53.2%, p=0.004). No significant differences in diagnostic yield were detected between “TBNA first” and “Cryobiopsy first” groups. We observed two cases of pneumothorax and one case of pneumomediastinum. - Conclusions Transbronchial cryobiopsy performed under EBUS guidance is a safe and useful approach that offers diagnostic histological samples of mediastinal lesions. - Tweetable abstract ERSpublications - click to tweetEBUS-guided transbronchial mediastinal cryobiopsy is a safe and promising novel diagnostic tool for mediastinal diseases that might allow for better histopathological evaluation and advanced testing https://bit.ly/3uiLkiD